A Unique Review Strategy that Motivates Student Learning - Donald L. Williams, EdD (Park University, 2007)
The use of educational games such as crossword puzzles, word search puzzles, modified television game shows, or commercial board and card games are attempts to make learning more fun and motivational regardless of the level of educational experience. This article explains how I have employed the melding of many of these games into one motivational and educational strategy. Students who faithfully availed themselves of the activities consistently improved their test scores and their overall grades within the course.